BIOTECHNOLOGICAL FACTORS OF BEES’ ETHOLOGY DURING NECTAR COLLECTION - Bezpalyi, I. F.; Postoіenko V. O.; Polishchuk, A. A. (Scientific Progress & Innovations, 2021)
The purpose of this work is to study the influence of biotechnological factors, such as the species composition of honey bearing plants and genuineness of bee families, on the ethology of bees in the pr ocess of collecting nectar. The breed of bees was determined by a complex of features: the visual method – by behavior, color and features of the body hairiness; physiological – honeycomb capping, animosity, swarming and bio-morphometric indicators. The accounting of the daily honey collection was carried out by the method of the control family, weighing the hives on the scales after the end of bees’ flying, and the obtained marketable honey – by weighing the honeycombs taken from the nest before and after extracting the product. It has been found that according to the given characteristics, the studies were carried out with the use of Ukrainian steppe bees. The following most typical exterior features of the breed were detected, namely, the proboscis length from 6.34 to 6.44 mm, the cubital index in the range of 2.17±0.04 – 2.61±0.05, discoidal displacement – 76–100%, edge shape of the wax plate – 68–96% of convex cases. The species composition of honey bearing plants was analyzed under typical conditions of honey flow in the Forest-Steppe zone of Ukraine and their contribution to the total honey flow during the entire beekeeping season. Conveyor flowering of honey bearing plants begins with forest miscell aneous herbs, willows, horticultural crops, winter rape. In summer, the main honey flow is provided by acacia, linden, buckwheat, and sunflower. Under favorable weather conditions, in aggregate, these honey bearing plants provide a continuous increase in feed stocks, on average, 200–400 g per day. Under honey flow conditions, strong bee families collected up to 20 kg of marketable honey from white acacia, 15–17 kg from linden, 9–10 kg from winter rape, 12–15 kg from buckwheat and 11–13 kg from sunflower. It has been shown that the quantitative characteristics of honey accumulation in a bee nest depend on a number of biotechnological factors. The main indicators that affect the ethology of bees when collecting nectar are genuineness and species composition of honey bearing base. The results of the conducted studies substantiate the subsequent research of the ethology of the Ukrainian steppe bee breed during honey flow, its popularization and the use in large apiaries (100 or more families) accor ding to the plan of breed zoning in the conditions of the Forest-Steppe zone of Ukraine.